Applicability of geotechnical approaches and constitutive models for foundation analysis of marine renewable energy arrays. (May 2017) - Heath, Jason E.; Jensen, Richard P.; Weller, Sam D.; Hardwick, Jon; Roberts, Jesse D.; Johanning, Lars
Abstract: For Marine Renewable Energy (MRE) to become a viable alternative energy source, it must encompass large arrays of devices. Arrays may include 1000s of devices. The associated foundations or anchors may encounter a range of seafloor sediment types and geotechnical properties. Wave and tidal energy convertors induce unique loads on foundations and anchors that are different from other seafloor engineering applications. Thus, there is a need for a combination of advanced site analysis and performance assessment. Geotechnical engineering plays the vital role of ensuring that foundation and anchor systems perform successfully for MRE devices. Our paper reviews the unique frequency and magnitude of loading regimes experienced by MRE arrays. We examine potential loading conditions on the foundation-anchor systems. Loading regimes include environmental and system loads from single devices or arrays of devices. We present specific load examples from field data. We explore the applicable geotechnical approaches to address these conditions, including constitutive models that may or may not adequately capture the response of the seafloor sediments to the MRE loads. Partially to fully dynamic constitutive model formulations may be necessary to properly model sediment-fluid hydromechanical response to MRE loading. Spacing of full MRE arrays and spatial variability in sediment properties may require multiple foundation types.